The Level Of Welfare Of Cattle Traders In Masbagik District Of East Lombok Regency Is An Islamic Economic Perspective - Nurfitri Hidayanti; Ahmad Hulaimi (Journal of Sharia Economy and Islamic Tourism, 2021)
Abstract: Research wants to find out the Level of Welfare of Cow Traders in Masbagik Subdistrict of East Lombok Regency from the eyeglasses of Islamic Economics. This research uses qualitative research methods, because it examines realities, phenomena or symptoms that are holistic / whole, complex, dynamic, meaningful and researchers as human instruments. Primary data collection is done under natural conditions. Data collection techniques are carried out by means of participatory observation, in-depth surveillance and decomentation techniques in the form of voice recordings, photos and some other documentation. Informants are selected before researchers go down to the lepangan and during their time in the field, using the 'snowboll sampling' technique.Researchers found that from the study of the Level of Welfare of Cow Traders in Masbagik District of East Lombok Regency from the eyeglasses of Islamic Economics is honesty, loose and generous and builds good relationships. While the principle of Islamic business ethics that has been applied by cow traders is the principle of not swearing falsely and not reneging on promises. In terms of welfare, not all cattle traders in Masbagik District of East Lombok regency get Good relationship. While the principle of Islamic business ethics that has been applied by cow traders is the principle of not swearing falsely and not reneging on promises. In terms of welfare, not all cattle traders in Masbagik District of East Lombok regency get Islamic welfare because it has not met the needs of their dharuriyat. But they said they were happy, having been grateful for the rizqi he received and had earned a good life (hayaatan tayyibah) in accordance with the maqasid shari'ah.Abstrak: Penelitian ingin mengetahui Tingkat Kesejahteraan Pedagang Sapi Di Kecamatan Masbagik Kabupaten Lombok Timur dari suduk kacamata Ekonomi Islam. Penelitian ini menggunakan metode penelitian kualitatif,. Teknik penelitian menggunakan ‘snowboll sampling”. Peneliti menemukan bahwa dari kajian terhadap Tingkat Kesejahteraan Pedagang Sapi Di Kecamatan Masbagik Kabupaten Lombok Timur.